Edukasi Pengukuran Tumbuh Kembang Anak Dengan Metode Pemeriksaan Ddst-Ii Pada Balita Di Wilayah Kerja Puskesmas Ralla Kabupaten Barru - Rizky Auliah Juniarti; Riswanti Riswanti; Baso Witman Adyaksa; Nasmirah Nasmirah; Desy Ratnasari; Andi Andira Dewi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Monitoring a child's growth and development is essential for every parent. Ideally, this should be done every three months as an early detection measure for developmental delays. One early detection method that can be used is the DDST II. The purpose of this activity was to measure children's growth and development using the DDST II examination method in the Ralla Community Health Center (Puskesmas) in Barru Regency. Twenty toddlers participated in this activity. The DDST II method assesses four aspects of child development: personal-social, fine motor skills, language, and gross motor skills. The results of this activity indicate whether the child's development is appropriate for their age or if there are any delays. If there are delays, parents will be provided with motivation and education to stimulate their child. A re-examination at the nearest Puskesmas will be recommended one week later.